Anti-glomerular basement membrane disease superimposed on membranous nephropathy after coronavirus disease 2019: A case report - Rongrong Hu; Siqi Tang; Chao Li; Yizhen Wei; Peng Xia; Ke Zheng; Yan Qin (Journal of International Medical Research)
Membranous nephropathy concurrent with anti-glomerular basement membrane disease is rarely reported. Acute kidney injury is prominent when these diseases coexist. Coronavirus disease 2019 may trigger this superimposition. Herein, we report the case of a 60-year-old woman with pathologically confirmed anti-phospholipase A2 receptor–associated membranous nephropathy. She experienced complete remission of membranous nephropathy after non-immunosuppressive treatment. One month before admission, she experienced fever and her coronavirus disease 2019 antigen test was positive. She developed gross hematuria, progressively worsening fatigue, and poor appetite, even after the coronavirus disease 2019 antigen test returned negative. Her urinalysis showed positive proteinuria and hematuria. Her serum creatinine levels increased rapidly. Her anti-phospholipase A2 receptor antibody was borderline positive. Anti-glomerular basement membrane disease was diagnosed with high anti-glomerular basement membrane antibody titer. She responded well to corticosteroids, cyclophosphamide, and plasmapheresis. We further reviewed several cases of concurrent anti-glomerular basement membrane disease and membranous nephropathy. Phospholipase A2 receptor positivity was not rare in these patients, and their renal outcome was not optimistic. Thus, when the clinical manifestation changes in patients with pathologically confirmed glomerular disease, superimposition on other disease should be considered.